ESTUDO DA CAMADA TRATADA GERADA POR REFUSÃO SUPERFICIAL A LASER DA LIGA AL-1,5%FE - Bertoni, Jean Cleber (2015)
There are currently extensive research on aluminum alloys, mainly due to its wide application in the automotive and aerospace industries, due to the following characteristics, among them, low density, high thermal conductivity and high corrosion resistance at room temperature. Al-Fe alloys have a high degree of microstructural change due to changes in their properties when appropriate techniques are applied. The Al-Fe alloy was studied in the composition of 1.5% Fe by weight, which was subjected to the treatment laser surface remelting in order to enhance its surface characteristics. The characterization of these alloys in order to determine the variation of the chemical composition at different depths was performed by Grazzing incidence x-ray diffraction (GIXRD). In this technique, the angle of incidence of the X-ray beam was fixed and the detector moved in 2θ, it is possible to obtain the XRD patterns at different depths by varying the angle of incidence. In this work, the characterizations the micro and nano structural sample of alloy Al-1.5wt.%Fe treated by laser surface remelting (LSR) were performed, on the treated surface, as well as the transverse section, this study was performed at treated samples surface and at the isolated weld fillet on samples, where were applied laser beam speeds of 20, 40 and 60 mm / s. In this study we used different characterization techniques, such as, optical microscopy, scanning electron microscopy, energy dispersive spectroscopy, together with atomic force microscopy, and the Vickers hardness. Also in this work the technique of GIXRD was used to obtain depth profiles of near the surface chemical composition of the alloy. The analysis was performed in the micrometer range varying the angle of incidence between 0.5° to 6° in steps of 0.5° and analysis with incident angles 3° and 6° in steps of 0.02° for each 10 sec. As a result by examining the microstructure was characterized melted zone, the heat affected zone and the substrate, a particular features were found for each velocity of the laser beam, generally the treated area showed a more homogenous microstructure consisting of grains smaller feature, with low roughness and high hardness. The heat affected zone was more notorious the morphology of grains elongated feature in the treated and untreated interface for low laser beam scanning velocities. By means of the technique of X-ray diffraction various metastable phases were found, such as aluminum oxide, nitrides, etc., with different intensities of peaks as a consequence of the variation of angle of incidence.